PENGARUH DERAJAT KEGANASAN TUMOR TERHADAP POLA GAMBARAN EEG PADA PENDERITA TUMOR OTAK PRIMER DI SUMATERA SELATAN - Wilasari Novantina; Yunni Diansari; Sri Handayani; Achmad Junaidi; Aspitriani Aspitriani; Irsan Saleh (NEURONA, 2020)
Introduction: Brain tumor is one of the major malignancies with high morbidity and mortality. Treatment options and prognosis in patients with primary brain tumors based on the type and degree of malignancy. Definitive diagnosis and degree of malignancy in patients with primary brain tumors obtained from histopathological features. But unfortunately, histopathological features are not always available in all primary brain tumor sufferers. Electrenefalography (EEG) examination is a non-invasive examination that can record biological activity and neuron changes in brain cells. Brain tumor itself is an abnormal mass in the brain tissue that interferes with the electrical and biological activity of normal cells in the brain. Aim: To determine the association between the degree of malignancy of brain tumors and EEG patterns in patients with primary brain tumors in RSUP Dr. Mohammad Hoesin Palembang. Methods: This was a cross sectional study. The study sample was primary brain tumor patients who had undergone surgery and had EEG record and histopathological features.Data were analysed using SPSS 22. Results: The data obtained from 36 samples consist of 30 samples of low grade brain tumor patients, and 6 high grade brain tumor patients. There was a weak correlation between the degree of malignancy with focal slowing EEG pattern (r = 0.378; p = 0.014). There was no correlation between the degree of malignancy with epileptiform discharge (r = 0.177; p = 0.281), focal slowing accompanied by epileptiform discharge (r = 0.215; p = 0.187) ) and normal EEG (r = 0.110; p = 0.506). Discussion: The focal slowing EEG pattern has a correlation with the degree of malignancy. This is due to changes in peri-tumoral metabolism which is common in brain tumors Keywords: brain tumor, eeg pattern, degree of malignancy